Analysis of the Implementation of Standard Operating Procedures (SOP) for New Patient Admissions at Siti Halimah Kandangan Hospital - Yusuf, Moch. Naufal Ferdian; Fauji, Diah Ayu Septi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: To analyze the implementation of SOP for accepting new patients at Siti Halimah Kandangan Hospital. Approach: This study uses a qualitative approach with descriptive methods. Data were collected through interviews, observations, and documentation and analyzed using triangulation. Research Findings: The results show that the implementation of SOP at Siti Halimah Kandangan Hospital is quite good, but there are challenges in the speed of service, communication with patients, supporting facilities, and technical constraints. Theoretical contribution/Research originality: This study provides a theoretical contribution to understanding the implementation of SOP in local hospitals, which has not been widely studied before. Practical/ Policy Implications: This study recommends staff training, facility improvements, and technology integration to improve the implementation of SOPs and the quality of health services. Research limitation: This study's limitations include that the data collection process may have been influenced by the researcher's perspective, potentially affecting the analysis's results. The researchers also recommend a future research agenda to investigate specific challenges in implementing SOP and how they impact patient experience.